-1x-9=7x+5

Simple and best practice solution for -1x-9=7x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1x-9=7x+5 equation:


Simplifying
-1x + -9 = 7x + 5

Reorder the terms:
-9 + -1x = 7x + 5

Reorder the terms:
-9 + -1x = 5 + 7x

Solving
-9 + -1x = 5 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-9 + -1x + -7x = 5 + 7x + -7x

Combine like terms: -1x + -7x = -8x
-9 + -8x = 5 + 7x + -7x

Combine like terms: 7x + -7x = 0
-9 + -8x = 5 + 0
-9 + -8x = 5

Add '9' to each side of the equation.
-9 + 9 + -8x = 5 + 9

Combine like terms: -9 + 9 = 0
0 + -8x = 5 + 9
-8x = 5 + 9

Combine like terms: 5 + 9 = 14
-8x = 14

Divide each side by '-8'.
x = -1.75

Simplifying
x = -1.75

See similar equations:

| 75=25*t+0.5*9.8*t^2 | | 9(x+4)+x=3(x+5)-8 | | -5(y-3y)+9=3(2y-y)+1+12y | | .50c+.40-400=190 | | 0.05x-2.75=0.3(x-5) | | 3=-3(x+4) | | -1x+9=7x+5 | | 6x+2-15=-15 | | .50c+.40=400 | | -3(x+4)+4=7(x+4)+3 | | 5(x-7)+10=3(x-5) | | h(t)=2t-t^2 | | 5sinx+7cosx=8 | | 12x-8=9x-8 | | x-4=-24-9x | | .50c+400=.40 | | (2x-5)=15 | | -3(t-5)+7t=6t-5 | | 2=x/6.4 | | 6-14=6+(-8) | | (a^4+4a+-8)=0 | | 12x^2y+18xy-6x=0 | | f(x)=15x^4-15x^2 | | a^4+4a-8=0 | | 45=7-2b | | 1/4x0.04 | | 12/7=k//8 | | .50c+.40=190 | | -4=6+2x | | 1.7=k/8 | | Log(x)=-8 | | r-9.8=-2.4 |

Equations solver categories